Effect of Entrepreneurship Learning on Interest in Entrepreneurship (Case Study in Management, Accounting, and Sociology Student, University of Bangka Belitung) - Mrs Christianingrum; Erita Rosalina (Integrated Journal of Business and Economics (IJBE), 2017)
This study aims to determine the influence of entrepreneurship learning on entrepreneurship interests (case study on student management, accounting and sociology, University of Bangka Belitung). This study is expected to be useful and provide an idea of the extent to which entrepreneurial learning can affect interest to entrepreneurship. To foster entrepreneurship interest in the students, lecturers are expected to be able to provide entrepreneurial learning that is able to make students interested in doing entrepreneurship activities. Through entrepreneurial learning, students are invited and directed to be able to open their insights about how entrepreneurial means. Because entrepreneurship can be a potential to be able to provide a good life on the current world job conditions. Objects in this study were 76 students consisting of students of Management, Accounting and Sociology. The research method using Simple Linear Regression Analysis Method to perform data analysis. The results showed that learning Entrepreneurship gives a positive influence to cultivate interest in entrepreneurship.